Immobilized Microbial Catalytic Oxidation Preparation and Application of Biopolymeric Ferric Sulfate - Xiaohui Xu; Min Lu; Liu Yang; Xiaohui Guan (Journal of Chemistry)
A novel inorganic polymer flocculant, biopolymeric ferric sulfate (BPFS), was prepared by immobilization technology of microorganisms and by oxidation of ferrous sulfate using domestic Thiobacillus ferrooxidans (T. f) under acidic condition. T. f was isolated on the agarose single-plate medium, which exhibited an unusual trait on the utilization of low concentration of the nitrogen source and phosphorus as the nutrient substance. Under the optimal conditions, the microorganism could grow and reproduce normally and maintain the strong catalytic oxidation activity to Fe2+. The immobilization of T. f on the polyurethane as the support matrix was investigated. Cycling batch operation was applied to the preparation of 40 kg/m3, 60 kg/m3, and 80 kg/m3 BPFS when the optimal conditions are pH value of 1.8, circulation flow rate of 0.28–0.30 L/h, and reaction temperature of 28 ± 1°C. When the prepared BPFS and SPFS (solid biopolymeric ferric sulfate) were used to dispose Songhua River water, the removal rate of turbidity and CODMn of BPFS was slightly better than that of SPFS. The removal efficiencies of turbidity and CODMn by BPFS could reach 93.9% and 79.7%, respectively. The result suggests that the BPFS has good flocculating activity.